KARAKTERISTIK PERJANJIAN BANGUN GUNA SERAH - Setlight, Mercy M. M. (LEX ET SOCIETATIS, 2013)
The objective is to determine the legal characteristics Agreement To Deliver Build (Build Operate and Transfer Contract / BOT) related to the presence of the Government as one of parties to the contract. This writing method by normative literature. research was conducted on the principle of the rule of law and the applicable law in BOT agreement. The results showed that the characteristics of the BOT Agreement is an agreement hybrid because Â mixture of public law and private law, in addition to the BOT Agreement is an agreement for a treaty policies implemented by local governments from the authority granted by law to act freely within the interest and protection to the people.